Analisis Studi Kelayakan Bisnis Ditinjau dari Aspek Pemasaran pada UMKM FLC Black Coffe Specialist Desa Menunggal, Kecamatan Kedamean, Kabupaten Gresik - Kusuma, Fika Widya (Seminar Nasional Manajemen, 2025)
This study aims to analyze the feasibility of FLC Black Coffee Specialist SME’s in Menunggal Village, Gresik, particularly from a marketing perspective, with the aim of assessing their performance and designing development strategies. The method used is a qualitative approach through observationand interviews. The findings show that robusta coffee products with distinctive flavorsandtheimplementation of door-to-door marketing strategies have successfully reached the local market effectively. Sales projections also show a positive trend until 2026. SWOT analysis confirms that product advantagesand opportunities for cooperation are major factors that outweigh weaknesses related to packaging and location. Overall, the marketing aspects are considered feasible with practical recommendations for packaging improvements and market expansion. However, this study has limitations in terms of generalization due to its local scope. In conclusion, this SME’s has a strong marketing foundation for further development, while also opening opportunities for further research involving financialand digital marketing aspects.